PERILAKU BALOK PROFIL DOUBLE KANAL (C) FERROFOAM CONCRETE DENGAN PLAT BAJA DAN BAUT SEBAGAI ALAT PENYAMBUNG (STUDI KASUS : VARIASI JUMLAH BAUT PADA SAYAP PROFIL - Sornia Derni; Muhammad Afifuddin; Abdullah Abdullah (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Construction of the bridge generally and especially the bridge girders made of steel, wood and concrete materials. The ferrocement technology is not as popular yet as reinforced concrete. In fact, this technology is more economical and can be applied to various things. Now ferrocement technology has been applied in various types and structures in various parts of the country. The use of lightweight concrete in earthquake prone areas is a good alternative, this is because the lightweight concrete can reduce the risk that will be caused by the earthquake. The purpose of this study was to determine the strength of the cross section of the ferrofoam concrete channel beam profile with the addition of pozzolan to the variation of the number of bolt connectors on the profile wing. Then the profile with variation of number of bolts ie: 2 bolts (2 specimens) and 4 bolts (2 specimens) 1 each (test specimen) using a join plate on the side of the body and 1 (specimen) not wearing a joint plate on the body. While the test object that uses 6 bolts (1 specimen) is treated without using the body connector plate. Concrete is planned to have compressive strength (f'c) 35 MPa and steel used is D8 threaded iron. The results of the study were 450.6 larger capacity 103% compared to the 450.2A profile. Unlike the case with the 450.4A profile after receiving the maximum load the load slowly drops until the test is stopped, capacity 450.4A is 89% greater than the 450.2A profile.